Rosc '77. : The poetry of vision. - Rosc Dublin 1977; Hugh Lane Municipal Gallery of Modern Art, Dublin; National Museum of Ireland, Dublin (Dublin : Cultural Committee of Dublin, 1977)
Arroyo, Eduardo ; Barré, Martin ; Bernik, Janez ; Beuys, Joseph ; Biasi, Alberto ; Boltanski, Christian ; Broodthaers, Marcel ; Caro, Anthony ; Caulfield, Patrick ; Ceroli, Mario ; Christo ; Coleman, James ; Colombo, Gianni ; Dibbets, Jan ; etc.
Rosc '77 : Modern Art - Early Animal Art, Hugh Lane Municipal Gallery of Modern Art, Dublin / National Museum of Ireland, Dublin, 21 August - 30 October 1977
boek